2008 6th National Conference on Telecommunication Technologies and 2008 2nd Malaysia Conference on Photonics 2008
DOI: 10.1109/nctt.2008.4814289
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency in MAC 802.15.4 for Wireless Sensor Networks

Abstract: Recent technological advances in sensors, low power integrated circuits, and wireless communications have enabled the design of low-cost, lightweight, and intelligent physiological sensor nodes. The IEEE 802.15.4 is a new wireless personal area network designed for wireless monitoring and control applications. The fast progress of research on energy efficiency in wireless sensor networks, and the need to compare with the solutions adopted in the standards motivates the need for this work. In the analysis prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…From the performance evaluation aspect, Ghazvini et al [23] suggested an energy efficient MAC protocol, based on IEEE 802.15.4, for WSNs that reduces energy depletion and network collisions by permitting devices to move between sleep and listening modes during the active period, when they have no packets to transmit. After that, Xiao et al [24] also proposed a Markov model that took into consideration the sleep-based mode of the beacon-enabled IEEE 802.15.4 standard.…”
Section: A Analytical-based Mac Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the performance evaluation aspect, Ghazvini et al [23] suggested an energy efficient MAC protocol, based on IEEE 802.15.4, for WSNs that reduces energy depletion and network collisions by permitting devices to move between sleep and listening modes during the active period, when they have no packets to transmit. After that, Xiao et al [24] also proposed a Markov model that took into consideration the sleep-based mode of the beacon-enabled IEEE 802.15.4 standard.…”
Section: A Analytical-based Mac Protocolsmentioning
confidence: 99%
“…The channel utilisation (ρ) for one superframe is defined as the summation of the time during the successful transmission of packets to the total time during one superframe (SF duration ). The ρ in the simulation can be mathematically evaluated as: (23) and SF duration can be clarified as…”
Section: Channel Utilisationmentioning
confidence: 99%
“…Analogous methods are used in [24, 25] to evaluate the power consumption. However, we assume that the sleep and idle mode energy consumption can be ignored which is because that power consumption in the sleep/idle mode for a short period is too small to measure.…”
Section: The Dynamic Topology Reformation Algorithm (Dtra)mentioning
confidence: 99%